Charge transfer processes in CsI:Tl using near-UV light; Journal of Luminescence; Vol. 155 - Yakovlev V. Yu. Viktor Yurjevich; Trefilova L. N. Larisa Nikolaevna; Мелешко А. А. Анна Алексеевна; Alekseev V. D. Vadim Dmitrievich; Kosinov N. N. Nikolay Nikolaevich (2014, 2014)
Title screen